2006
DOI: 10.1055/s-2006-924254
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism following Severe Traumatic Brain Injury

Abstract: Although hypopituitarism is a known complication of traumatic head injury, it may be under-recognized due to its subtle clinical manifestations. To address this issue, we determine the prevalence of neuroendocrine abnormalities in patients rehabilitating from severe traumatic brain injury (Glasgow Coma Scale < or = 8). 76 patients (mean age 39 +/- 14 yr; range 18-65; 53 males and 23 females; BMI 25.8 +/- 4.2 kg/m2; mean +/- SD) with a severe traumatic brain injury, an average of 22 +/- 10 months before this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 19 publications
3
34
1
Order By: Relevance
“…This prevalence of hypopituitarism is much lower compared with the prevalence rates reported in the majority of the previous studies (15-90%) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This might be explained by the use of different endocrine tests and cutoff values (19).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This prevalence of hypopituitarism is much lower compared with the prevalence rates reported in the majority of the previous studies (15-90%) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This might be explained by the use of different endocrine tests and cutoff values (19).…”
Section: Discussioncontrasting
confidence: 58%
“…The available cohort studies investigating the prevalence of pituitary insufficiency report a percentage ranging from 15 to 90% (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). There are several explanations for this remarkably wide range in reported prevalence, including differences in inclusion criteria and duration of follow-up since TBI (short-versus longterm follow-up), and the use of different tests, and cutoff values (19).…”
Section: Introductionmentioning
confidence: 99%
“…Kelly and colleagues emphasized that also patients with subarachnoid haemorrhage (SAH) may also be at high risk for consequent hypopituitarism [12]. Following these, other important retrospective studies evaluated patients who had experienced brain injury more than a year before [13,17,18,[21][22][23][24], others tested patients early after TBI or SAH [13,[21][22][23][24]. The clinical relevance of brain-injury-induced pituitary dysfunction was underlined by all authors.…”
Section: Bi-related Hypopituitarism: When Does It Occur?mentioning
confidence: 99%
“…Ten systematic studies of endocrine function in a total of 749 patients in the chronic phase after admission for TBI (most patients were studied at least 6 months after trauma) [12][13][14][15][16][17][18][19][20][21] and five studies of 122 individuals with aneurysmal SAH [12,[22][23][24][25] have been published. The different prevalence of hypopituitarism reported in the above mentioned studies is probably due to the different study design (cross sectional vs prospective studies), the different time of evaluation after BI (from 24 h to 23 years), and the different protocol used to investigate hypopituitarism.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that these two problems may actually interact in complex and previously underappreciated ways. 1 A body of recent research has shown that TBIs, at all ranges of severity, have a negative effect upon pituitary function, which results in diminished levels of several endogenous Neuroethics DOI 10.1007/s12152-014-9215-2 hormones, such as growth hormone (GH) and gonadotropin [1][2][3][4][5][6][7][8]. Furthermore, emerging research suggests that hormone replacement therapy (HRT) is an effective treatment for symptoms caused by TBI-related hormone deficiency [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%